Mechanisms Involved in Childhood Obesity-Related Bone Fragility - Faienza, Maria Felicia; D'Amato, Gabriele; Chiarito, Mariangela; Colaianni, Graziana; Colucci, Silvia; Grano, Maria; Corbo, Filomena; Brunetti, Giacomina (Frontiers in Endocrinology, 2019)
Childhood obesity is one of the major health problems in western countries. The excessive accumulation of adipose tissue causes inflammation, oxidative stress, apoptosis, and mitochondrial dysfunctions. Thus, obesity leads to the development of severe co-morbidities including type 2 diabetes mellitus, liver steatosis, cardiovascular, and neurodegenerative diseases which can develop early in life. Furthermore, obese children have low bone mineral density and a greater risk of osteoporosis and fractures. The knowledge about the interplay bone tissue and between adipose is still growing, although recent findings suggest that adipose tissue activity on bone can be fat-depot specific. Obesity is associated to a low-grade inflammation that alters the expression of adiponectin, leptin, IL-6, Monocyte Chemotactic Protein 1 (MCP1), TRAIL, LIGHT/TNFSF14, OPG, and TNFα. These molecules can affect bone metabolism, thus resulting in osteoporosis. The purpose of this review was to deepen the cellular mechanisms by which obesity may facilitate osteoporosis and bone fractures.